Teori Biaya (Short Run Long-Run) - Nataline Simanjuntak; Irna Della Br Ginting; Pintar Padang; Ade Asminaria Sihombing; Excaudia Siringoringo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Cost theory is one of the fundamental concepts in economics that explains how firms allocate resources to produce goods or services. In economic analysis, costs are categorized into short-run and long-run costs. In the short run, there are inputs that are fixed, limiting the firm's ability to adjust the scale of production. This leads to the concepts of fixed costs and variable costs. In contrast, in the long run, all inputs are variable, giving firms full flexibility to adjust their scale of production, which results in the formation of the long-run cost curve. This curve serves as an envelope of various short-run cost curves and reflects production efficiency at different scales. Understanding the differences between short-run and long-run costs is essential for firms in making decisions, particularly in production planning and long-term investment.